What are the risks and benefits of intrauterine device (IUD) insertion on the same day as office counseling?. Issue 2 (February 2018) - Lee, Katherine; Mounsey, Anne
Abstract : EVIDENCE‐BASED ANSWER : Risk of pelvic inflammatory disease (PID) does not differ between same‐day or delayed insertion for women without overt cervicitis (SOR: A, meta‐analysis of RCTs and prospective cohort). Same‐day insertion increases probability of continued IUD use compared with delayed insertion. However, women with same‐day insertion after an induced or spontaneous abortion are more than twice as likely to have IUD expulsion than women with delayed insertion (SOR: A, meta‐analysis of RCTs). Return rates for a subsequent appointment for IUD insertion are as low as 54% (SOR: B, cross‐sectional study). Delaying IUD placement for sexually transmitted disease testing is discouraged in asymptomatic patients (SOR: C, consensus opinion).